Innovative financing for rural surgical patients: Experience in mission hospitals - Gnanaraj Jesudian (CHRISMED Journal of Health and Research, 2016)
In rural India most of the surgical patients become impoverished due to surgical treatment pushing several families below poverty line. We describe the various methods that we tried to help these patients pay for the surgical procedures without becoming impoverished. Some of them were successful and many of them were not so successful. The large turnover and innovative methods helped the mission hospitals to serve the poor and the marginalized. Some of these methods might not be relevant in areas other than Northeast India while many could be used in other areas.